# Solve says my system of equations has no solution

I got a system like this (just for example): I need to get some of the variables expressed in a form like the following.

x == (z - z1) Tan[α1q - μ ] + x1

Let's say that x and σ are required. I write the following code:

eq1 := (x - x1) == (z - z1) Tan[α1q - μ ];
eq2 := (x - x2) == (z - z2) Tan[α2q - μ ];
eq3 := (σ - σ1) + 2 σ1q Tan[ϕ] (α - α1) == γ (z - z1 - (x - x1) Tan[ϕ]);
eq4 := (σ - σ2) + 2 σ2q Tan[ϕ] (α - α2) == γ (z - z2 - (x - x2) Tan[ϕ]);
system1 := {eq1, eq2, eq3, eq4};
Solve[system1, x]


Evaluation gives me just {}. How to make this request correct?

UPD got different outputs in notebooks and none of them is what I really want. • the question is ill posed. You have four equations and so to satisfy all you will need to solve for four variables ( Pick any four that do not live inside the trig funcions and you should get a nice result ) – george2079 Feb 9 '17 at 15:47

I think MMM is being ingenuous. Reduce returns a rather complicated expression with a lot of conditionals (24 of them). It turns out that the equation for x is same under all the conditions. So I think I need to show a little more work than MMM did.

eq1 = (x - x1) == (z - z1) Tan[α1q - μ];
eq2 = (x - x2) == (z - z2) Tan[α2q - μ];
eq3 = (σ - σ1) + 2 σ1q Tan[ϕ] (α - α1) == γ (z - z1 - (x - x1) Tan[ϕ]);
eq4 = (σ - σ2) + 2 σ2q Tan[ϕ] (α - α2) == γ (z - z2 - (x - x2) Tan[ϕ]);
system1 = {eq1, eq2, eq3, eq4};


Note I do not use := here. It is inappropriate.

xeqs = Cases[Reduce[system1, x], x == _, ∞] // Union


{x == x2 + z Tan[α2q - μ] - z2 Tan[α2q - μ]}

This last shows that there is really only one solution, so what is wanted is

xeqs[]


x == x2 + z Tan[α2q - μ] - z2 Tan[α2q - μ]

• Not getting this. The result only satisfies one equation and if we are happy with that there are four results obtained by solving each equation individually for x. – george2079 Feb 9 '17 at 15:43

Try Reduce

eq1 := (x - x1) == (z - z1) Tan[α1 q - μ];
eq2 := (x - x2) == (z - z2) Tan[α2 q - μ];
eq3 := (σ - σ1) +
2 σ1q Tan[ϕ] (α - α1) == γ (z -
z1 - (x - x1) Tan[ϕ]);
eq4 := (σ - σ2) +
2 σ2q Tan[ϕ] (α - α2) == γ (z -
z2 - (x - x2) Tan[ϕ]);
system1 := {eq1, eq2, eq3, eq4};
Reduce[system1, x]


Learning from Pros is always helpful...

Reduce[system1, x] // Union // First


x == x1 + z Tan[q α1 - μ] - z1 Tan[q α1 - μ]

Collect[%, Tan[q α1 - μ]]


x == x1 + (z - z1) Tan[q α1 - μ]